2021
DOI: 10.3390/v13081521
|View full text |Cite
|
Sign up to set email alerts
|

Cannabis and Inflammation in HIV: A Review of Human and Animal Studies

Abstract: Persistent inflammation occurs in people with HIV (PWH) and has many downstream adverse effects including myocardial infarction, neurocognitive impairment and death. Because the proportion of people with HIV who use cannabis is high and cannabis may be anti-inflammatory, it is important to characterize the impact of cannabis use on inflammation specifically in PWH. We performed a selective, non-exhaustive review of the literature on the effects of cannabis on inflammation in PWH. Research in this area suggests… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 131 publications
0
11
0
Order By: Relevance
“…The use of cannabis is highly prevalent in people living with HIV (PLWH), with cannabis use being reported to be 2-3 times higher than use among the general US population (Whit eld et al, 1997; Cristiani et al, 2004;Pacek et al, 2018;Ellis et al, 2021). Besides recreational use, PLWH report using cannabis to alleviate HIV-related symptoms, such as pain, anxiety, stress, nausea, and loss of appetite (Woolridge et al, 2005;Shiau et al, 2017;Costiniuk et al, 2019;Wardell et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…The use of cannabis is highly prevalent in people living with HIV (PLWH), with cannabis use being reported to be 2-3 times higher than use among the general US population (Whit eld et al, 1997; Cristiani et al, 2004;Pacek et al, 2018;Ellis et al, 2021). Besides recreational use, PLWH report using cannabis to alleviate HIV-related symptoms, such as pain, anxiety, stress, nausea, and loss of appetite (Woolridge et al, 2005;Shiau et al, 2017;Costiniuk et al, 2019;Wardell et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…56 Research in this area suggests that cannabinoids are anti-inflammatory in the setting of HIV through the effect of the endocannabinoid system in the gut and through stabilization of gut-blood barrier integrity. 57 Fulcher et al revealed that MJ use in HIV patients is positively correlated with the increase of Fusobacterium and Anaerotruncus and negatively associated with the decrease in the abundance of Dorea organism. 47 Typically, MJ users in HIV patients engage in higher-risk sexual conduct or practices leading to bacterial vaginosis (BV) which is found to be characterized by the lack of Lactobacilli and the overgrowth of facultative anaerobic organisms.…”
Section: Discussionmentioning
confidence: 99%
“…Although mostly based on non-randomized studies with no comparators, a recent systematic review also shows that using cannabis by patients with post-traumatic stress disorder (PTSD) improves pain and sleep and is associated with reduced overall PTSD symptoms and reports of a better quality of life [31,32]. Likewise, cannabis provides a beneficial intervention for reducing inflammation-related morbidity in acquired immunodeficiency syndrome (AIDS) patients [33], also improving muscle and nerve pain, and may also assist with depression [34][35][36]. In multiple sclerosis patients, cannabis reduces spasticity compared to placebo [37][38][39].…”
Section: Neuropathic Neurological and Hiv-related Symptomsmentioning
confidence: 99%